Análisis de rentabilidad financiera en la Unidad de Hemodiálisis Dial-Ríos, de la ciudad de Babahoyo, año 2020 - Santamaría Ramírez, Elsa Adriana (2021)
The present investigative work, which is part of the final titration process, is based on an analysis carried out on the profitability of the year 2020, which was carried out by the Hemodialysis Unit of the province of Los Ríos, located in the city of Babahoyo. Private non-profit institution that is dedicated to helping people with serious kidney diseases, its clients being companies in the health area belonging to the public sector, such as the IESS, MSP, ISPOL, despite this the company has accounts receivable for $ 4'381,860.41 until December 31, 2020, leading them to have losses. Companies with non-profit activities are those that have a different objective than commercial companies, their main objective being to help a specific community, being thus their profitability is focused on how the allocated expenses manage to help performance administrative of the same. As the majority of clients, the patients who are sent by these institutions, the lack of collection of these accounts has generated that the profitability of the company is very low, preventing it from complying with debts acquired by the institution to cover the needs of its users, despite this there are companies that have begun to improve the cancellation process, such as the IESS, which makes payments after 15 days of debts.